PENGOLAHAN LIMBAH CAIR KOSMETIK SECARA ELEKTROKOAGULASI SISTEM BATCH - Sutanto .; Kareina Artanti (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2019)
The success of this electrocoagulation method wastewater treatment is influenced by the voltage density and contact time. A reddish liquid waste treatment from the cosmetics industry has been carried out by batch electrocoagulation system. The research aims to determine the optimum voltage and time density conditions that can be the result of effective cosmetics liquid waste treatment by batch system electrocoagulation method. Reddish cosmetics liquid waste samples were taken from the cosmetics industry and analyzed the parameters of waste water quality including: pH; dissolved oxygen (DO); Chemical Oxygen (COD) requirements for Fe and Al metal content, and then waste treatment is carried out. A total of 0.5 liters of waste samples were carried out by electrocoagulation of a batch system using a one liter volume glass chamber using 1 mm aluminum plate electrodes measuring 5 cm x 10 cm effectively immersed, the distance between the electrodes was 5 cm. Both electrodes were given varying electric voltages: 9; 12; 15; and 20 volts DC and each with time variations: 15; 30; 45; and 60 minutes, the experiment was repeated twice. Electrocoagulation water is analyzed a number of quality parameters according to the initial analysis. The best treatment optimum conditions produce water quality: pH = 9.96; DO = 6.9 mg / L; COD = 280 mg / L (a decrease of 74.19%); TSS = 88 mg / L (a decrease of 86.21%); Fe = 0.31 mg / L (80.38% Fe decrease). The results of this electrocoagulation treatment meet wastewater quality standards according to Permen LH No. 05 of 2014 annex XLVII class II except pH ( 9.0)., And can be discharged by water bodies.